The Development of Children Protection Institutions (CPIs) in Austria : How the influence of the 19th Century Merciful Sisters of Zams is still felt today - Weisseisen-Lund, Stefanie (My University, 2025)
In Austria, collective out-of-home care for children under age six dates to the 19th century. Circumstances such as industrialization and socioeconomic changes during the 18th and 19th centuries altered family structures and therefore required changes to how children would be cared for. For the first time, parents went to work outside the home in factories and other large-scale businesses and were left without care options for their children. These new circumstances led to child neglect and an increase in mortality rates. Despite these tragedies, the Austrian government did not establish care-based institutions for children below age six. To fill the need of care for children, Kinderbewahranstalten (Children Protection Institutions - CPIs) were established by private charities. A main reason for establishing these institutions was to protect the children of working-class families from neglect and socialize them as “good” citizens. Associations and individuals obtained permission from the Catholic Church to open institutions since the Church possessed the authority to establish protection institutions. The Merciful Sisters, a Catholic female order located in Zams, Tirol, played an important role in providing childcare for poor families in 19th century Austria. The denomination established one of Austria’s first private schools to educate kindergarten teachers in 19th century. Concurrently, other female orders in Austria developed similar approaches to childcare and opened CPIs in other parts of the Habsburg Empire thus providing nuns as child-carers. As of the time of publication of this thesis, the Merciful Sisters still exists and maintains the lineage that has shaped the modern educational system in Austria.
Keywords: children protection institutions, childcare, Kinderbewahranstalten, Austria, Merciful Sisters, history, 19th century